Crystalline forms of GSK1278863, and preparation method and pharmaceutical use thereof

JP2025041663AInactive Publication Date: 2025-03-26GLAXOSMITHKLINE INTPROP (N 2) LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024211089
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-09-15
Filing Date
2024-12-04
Publication Date
2025-03-26
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 2025041663000021
    Figure 2025041663000021
  • Figure 2025041663000022
    Figure 2025041663000022
  • Figure 2025041663000023
    Figure 2025041663000023
Patent Text Reader

Abstract

To provide crystalline forms of a hypoxia-inducible factor prolyl hydroxylase inhibitor compound (I) GSK1278863, and a preparation method and use thereof.SOLUTION: The invention provides: a crystalline form CS1 of N-[(1,3-dicyclohexylhexahydro-2,4,6-trioxopyrimidin-5-yl)carbonyl]glycine, where the X-ray powder diffraction pattern has characteristic peaks at 2θ values of 6.4°±0.2°, 7.5°±0.2°, 7.9°±0.2° using CuKα radiation; a preparation method thereof; and a pharmaceutical formulation for treating and / or preventing anemia.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of pharmaceutical crystal technology, in particular to crystalline forms of hypoxia-inducible factor prolyl hydroxylase inhibitors and their preparation methods and uses. [Background technology]

[0002] GSK1278863 (Daprodustat) is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor developed by GlaxoSmithKline for the treatment of anemia, including anemia associated with chronic kidney disease.

[0003] Until now, the standard treatment for chronic kidney disease-related anemia is injection of recombinant human erythropoietin. Injection of high molecular weight recombinant human erythropoietin is often accompanied by cardiovascular safety issues. GSK1278863 is a small molecule oral hypoxia-inducible factor prolyl hydroxylase inhibitor that can promote the production of red blood cells that carry oxygen to the necessary parts of the body by inhibiting prolyl hydroxylase, thereby alleviating anemia. This is similar to the effect that occurs in the body of humans at high altitude. In clinical practice, GSK1278863 has shown excellent anemia alleviation effect and safety, and its effect is equivalent to that of injectable recombinant human erythropoietin, with higher safety. In addition, oral formulation of GSK1278863 is more convenient to administer to patients compared with injection of high molecular weight recombinant human erythropoietin.

[0004] The chemical name of GSK1278863 is N-[(1,3-dicyclohexylhexahydro-2,4,6-trioxopyrimidin-5-yl)carbonyl]glycine (hereinafter referred to as “Compound (I)”), and its structural formula is as follows:

[0005] [ka]

[0006] In the field of pharmaceutical research, the color, melting point, solubility, dissolution, chemical stability, mechanical stability, etc. of a drug vary depending on the crystalline form of the drug, and these properties affect the quality, safety, and efficacy of pharmaceutical preparations, leading to differences in clinical efficacy. Therefore, research and control of crystalline forms is important for the development of medicines. This is an important research topic in drug development.

[0007] Up to now, there has been no report on the crystal form of GSK1278863. Patent CN101505752B discloses the chemical structure and preparation method of GSK1278863, but the present inventors reproduced the preparation method to obtain a solid of GSK1278863, and found that the solid had low purity, very high impurity content, and high hygroscopicity, making it unsuitable for pharmaceutical use. The present inventors have found crystalline forms CS1 and CS9 of GSK1278863 with excellent properties. Compared with conventional solids, the crystalline forms CS1 and CS9 of GSK1278863 of the present invention have high purity and lower hygroscopicity. In addition, the new crystalline forms of the present invention have good stability, are not easily decomposed, have excellent solubility and flowability, and have ideal in vitro dissolution properties for formulations, which can provide a better option in terms of the preparation of pharmaceutical formulations containing GSK1278863, and are of great importance in pharmaceutical development. Summary of the Invention [Problem to be solved by the invention]

[0008] The main object of the present invention is to provide a crystalline form of GSK1278863 and a method for preparing and using the same. [Means for solving the problem]

[0009] According to the objective of the present invention, the present invention provides crystalline form CS1 of compound (I) (hereinafter referred to as "crystalline form CS1").

[0010] The crystalline form CS1 has characteristic peaks in the powder X-ray diffraction pattern using Cu-Kα radiation at 2θ values ​​of 6.4°±0.2°, 7.5°±0.2°, and 7.9°±0.2°.

[0011] Furthermore, the crystalline form CS1 has characteristic peaks in its powder X-ray diffraction pattern at one or more 2θ values ​​of 17.2°±0.2°, 21.0°±0.2°, 24.0°±0.2°, and 19.3°±0.2°. Preferably, the crystalline form CS1 has characteristic peaks in its powder X-ray diffraction pattern at all 2θ values ​​of 17.2°±0.2°, 21.0°±0.2°, 24.0°±0.2°, and 19.3°±0.2°.

[0012] In a preferred embodiment, the crystalline form CS1 has characteristic peaks in the powder X-ray diffraction pattern at 2θ values ​​of 6.4°±0.2°, 7.5°±0.2°, 7.9°±0.2°, 17.2°±0.2°, 21.0°±0.2°, 24.0°±0.2° and 19.3°±0.2°.

[0013] Although not limited thereto, in one embodiment of the present invention, the powder X-ray diffraction pattern of crystalline form CS1 is shown in FIG.

[0014] In accordance with the objectives of the present invention, the present invention further provides a method for preparing crystalline form CS1, which comprises the following method (1) or method (2): (1) GSK1278863 is dissolved in a cyclic ether solvent or a ketone solvent, and the mixture is evaporated and crystallized at 10 to 50°C to obtain the target compound. (2) GSK1278863 is dissolved in a cyclic ether solvent, a poor solvent is added to cause crystallization, and the desired product is obtained by separating and drying.

[0015] Furthermore, in the method (1), the cyclic ether solvent is preferably tetrahydrofuran, the ketone solvent is preferably one of acetone and methyl isobutyl ketone or any combination thereof, and the volatilization temperature is preferably room temperature or 50°C.

[0016] Furthermore, in the method (1), the ketone solvent is more preferably acetone or methyl isobutyl ketone.

[0017] Furthermore, in the method (2), the cyclic ether solvent is preferably 1,4-dioxane, the poor solvent is preferably water, and the crystallization time is preferably 0.5 to 24 hours.

[0018] Furthermore, in the method (2), the crystallization time is preferably 2 hours.

[0019] In accordance with the objectives of the present invention, the present invention further provides a crystalline form CS9 of Compound (I) (hereinafter referred to as "crystalline form CS9").

[0020] The crystalline form CS9 has characteristic peaks in the powder X-ray diffraction pattern using Cu-Kα radiation at 2θ values ​​of 4.6°±0.2°, 6.6°±0.2°, and 21.1°±0.2°.

[0021] Furthermore, the crystalline form CS9 has characteristic peaks in its powder X-ray diffraction pattern at one or more 2θ values ​​of 9.4°±0.2°, 20.2°±0.2°, and 24.2°±0.2°. Preferably, the crystalline form CS1 has characteristic peaks in its powder X-ray diffraction pattern at all 2θ values ​​of 9.4°±0.2°, 20.2°±0.2°, and 24.2°±0.2°.

[0022] In a preferred embodiment, the crystalline form CS9 has characteristic peaks in the powder X-ray diffraction pattern at 2θ values ​​of 4.6°±0.2°, 6.6°±0.2°, 21.1°±0.2°, 9.4°±0.2°, 20.2°±0.2° and 24.2°±0.2°.

[0023] Although not limiting, in one embodiment of the present invention, the powder X-ray diffraction pattern of crystalline form CS9 is shown in FIG.

[0024] In accordance with the object of the present invention, the present invention further provides a method for preparing crystalline form CS9, which comprises the following method (1) or method (2): (1) GSK1278863 is dissolved in an ether-based solvent, a polymer is added, and the target compound is obtained by volatilization and crystallization at 10 to 70°C. (2) GSK1278863 is dissolved in a mixture of ester and alcohol solvents, and the target compound is obtained by volatilization and crystallization at 10 to 70°C.

[0025] Furthermore, in the method (1), the ether solvent is preferably methyl tert-butyl ether, the polymer is preferably a polymer consisting of equal masses of polycaprolactone, polyoxyethylene, polymethyl methacrylate, hydroxyethyl cellulose and sodium alginate, and the volatilization temperature is preferably 50°C.

[0026] Furthermore, in the method (2), the ester-based solvent is preferably ethyl acetate, the alcohol-based solvent is preferably ethanol, the volume ratio of the ester-based solvent to the alcohol-based solvent is preferably 1:10 to 10:1, and the volatilization temperature is preferably 50°C.

[0027] Furthermore, in the method (2), the volume ratio of the ester solvent to the alcohol solvent is preferably 1:1.

[0028] The process for preparing crystalline forms CS1 and CS9 of the present invention comprises the steps of: The "room temperature" does not refer to an exact temperature value, but rather to a temperature range of 10 to 30°C.

[0029] In the present invention, the raw material GSK1278863 refers to its solid (crystalline or amorphous), semi-solid, wax or oil form.Preferably, the raw material compound (I) is in solid powder form.

[0030] In the present invention, "crystal" or "crystal form" refers to one that is confirmed by the characteristics of the X-ray diffraction pattern shown. Those skilled in the art will understand that the physicochemical properties referred to in the present invention are identifiable, and the experimental error depends on the conditions of the instrument, the preparation of the sample, and the purity of the sample. In particular, it is well known to those skilled in the art that X-ray diffraction patterns generally vary depending on the conditions of the instrument. In particular, the order of peak intensities should not be considered as the only or decisive factor, since the relative intensities of the X-ray diffraction pattern may also vary depending on the experimental conditions. In reality, the relative intensities of the diffraction peaks in the XRPD pattern are related to the preferred orientation of the crystal, and the peak intensities shown herein are illustrative rather than absolute. In addition, the experimental error of the peak angles is usually 5% or less, and the errors of these angles must also be taken into account, and an error of ±0.2° is usually allowed. In addition, experimental factors such as the height of the sample may cause an overall shift in the peak angles, and a certain degree of shift is usually allowed. Therefore, those skilled in the art will understand that the X-ray diffraction pattern of the crystalline form in the present invention does not necessarily match the X-ray diffraction pattern of the examples referred to in the present specification. As used herein, "the XRPD patterns are the same" does not mean absolute identity, but rather that the positions of the same peaks may differ by ±0.2°, and a certain degree of variability in peak intensity is allowed. Any crystal form having the same or similar pattern of characteristic peaks in these spectra falls within the scope of the present invention. By comparing the spectrum of the present invention with that of an unknown crystal form, a person skilled in the art can confirm whether the two sets of spectra represent the same or different crystal forms.

[0031] In some embodiments, the crystalline forms CS1 and CS9 of the present invention are pure and single and substantially free of other crystalline forms. In the present invention, "substantially free" in relation to the novel crystalline form means that the crystalline form contains less than 20% (by weight), in particular less than 10% (by weight), further less than 5% (by weight), and further less than 1% (by weight) of other crystalline forms.

[0032] It should be understood by those skilled in the art that the numerical values ​​and numerical ranges described in the present invention should not be interpreted in a narrow sense as numerical values ​​or numerical ranges themselves, and that they may vary slightly around such numerical values ​​depending on the specific technical environment, without departing from the spirit and principles of the present invention. In the present invention, such a range of variation that a person skilled in the art can foresee is often expressed by the term "about".

[0033] The crystalline form according to the present invention has the following advantageous effects: (1) Compared with the conventional technology, the crystalline forms according to the present invention have lower hygroscopicity. The weight gain of the conventional solid at 80% relative humidity is 1.14%, whereas the weight gain of the crystalline forms CS1 and CS9 according to the present invention at 80% relative humidity is 0.53% and 0.22%, respectively. Thus, there is almost no weight gain due to hygroscopicity, and the stability under high humidity conditions is very high, which is suitable from the viewpoint of long-term storage of drug substances and preparation of formulations. (2) Compared with the prior art, the crystalline form of the present invention has a higher purity. The prior art solid has a purity of 81.06% and a high content of impurities. In a specific embodiment, the purity of the crystalline form of the present invention is greater than 99%, and in another specific embodiment, the purity of the crystalline form of the present invention is greater than 99.5%. (3) The crystal forms CS1 and CS9 of the present invention have good stability. Form CS1 and crystalline form CS9 were stored in an open state at 25°C / 60% relative humidity, and accelerated conditions of 40°C / 75% relative humidity and 60°C / 75% relative humidity, and as a result, there was no change in the crystal form even after at least 3 months, and there was almost no change in the purity during storage. A pharmaceutical preparation containing crystalline forms CS1 and CS9 of the present invention mixed with an additive was stored for 1 month at accelerated conditions of 40°C / 75% relative humidity, and as a result, the crystal form of the present invention in the preparation remained unchanged. Since the stability of the crystal form according to the present invention is good, the uniformity of the quality of the sample is ensured, which is important for ensuring the efficacy and safety of the drug and preventing toxicity and adverse drug reactions caused by impurities. (4) The crystalline form of the present invention has good solubility in biologically relevant media and pure water, and therefore can ensure good dissolution of the crystalline form in the formulation, promote effective absorption of the active ingredient of the formulation in the body, and is useful for achieving ideal bioavailability and efficacy of the medicine. (5) The crystalline form of the present invention has better dissolution and higher dissolution rate when made into tablets. In a phosphate buffer medium of pH=6.8, the average dissolution rate reaches 67.7% at 10 minutes and 95.2% at 60 minutes. Good in vitro dissolution rate leads to higher drug absorption and better in vivo exposure characteristics, leading to higher bioavailability and drug efficacy. High in vitro dissolution rate allows the drug to reach its maximum plasma concentration quickly after administration, ensuring that the drug is effective quickly and enhancing its efficacy.

[0034] Furthermore, the present invention provides a pharmaceutical composition comprising a therapeutically and / or prophylactically effective amount of crystalline form CS1 or crystalline form CS9 according to the invention or any mixture thereof and at least one pharma- ceutically acceptable carrier, diluent or excipient.

[0035] Furthermore, the present invention provides the use of crystalline form CS1 or crystalline form CS9 or any mixture thereof for the manufacture of a medicament comprising a hypoxia inducible factor prolyl hydroxylase inhibitor.

[0036] Furthermore, the present invention provides the use of crystalline form CS1 or crystalline form CS9 or any mixture thereof for the manufacture of a medicament for the treatment and / or prevention of anemia. [Brief description of the drawings]

[0037] [Figure 1] FIG. 1 is an XRPD pattern of the crystalline form CS1 obtained in Example 1 of the present invention. [Diagram 2] FIG. 2 is a 1H NMR spectrum of the crystalline form CS1 obtained in Example 1 of the present invention. [Diagram 3] FIG. 3 is a DSC pattern of the crystal form CS1 obtained in Example 1 of the present invention. [Figure 4] FIG. 4 is a TGA pattern of the crystalline form CS1 obtained in Example 1 of the present invention. [Diagram 5] FIG. 5 is an XRPD pattern of crystalline form CS1 obtained in Example 2 of the present invention. [Figure 6] FIG. 6 is an XRPD pattern of the crystalline form CS9 obtained in Example 5 of the present invention. [Figure 7] FIG. 7 is a 1H NMR spectrum of the crystalline form CS9 obtained in Example 5 of the present invention. [Figure 8] FIG. 8 is a DSC pattern of the crystalline form CS9 of the present invention. [Figure 9] FIG. 9 is a TGA pattern of the crystalline form CS9 of the present invention. [Figure 10] FIG. 10 is a DVS pattern of the crystalline form CS1 of the present invention. [Figure 11] FIG. 11 is a DVS pattern of the crystalline form CS9 of the present invention. [Figure 12] FIG. 12 shows a conventional solid-state DVS pattern. [Figure 13] FIG. 13 shows an XRPD comparison of crystalline form CS1 of the present invention before and after 3 months of storage at 25° C. / 60% relative humidity (top: before storage, bottom: after storage). [Figure 14] FIG. 14 shows an XRPD comparison of crystalline form CS1 of the present invention before and after 3 months of storage at 40° C. / 75% relative humidity (upper figure: before storage, lower figure: after storage). [Figure 15] FIG. 15 shows an XRPD comparison of crystalline form CS1 of the present invention before and after 3 months of storage at 60° C. / 75% relative humidity (top: before storage, bottom: after storage). [Figure 16] FIG. 16 shows an XRPD comparison of crystalline form CS9 of the present invention before and after 3 months of storage at 25° C. / 60% relative humidity (top: before storage, bottom: after storage). [Figure 17] FIG. 17 shows an XRPD comparison of crystalline form CS9 of the present invention before and after 3 months of storage at 40° C. / 75% relative humidity (top: before storage, bottom: after storage). [Figure 18]FIG. 18 shows an XRPD comparison of crystalline form CS9 of the present invention before and after 3 months of storage at 60° C. / 75% relative humidity (top: before storage, bottom: after storage). [Figure 19] FIG. 19 is a dissolution curve of a tablet containing crystalline form CS1 of the present invention in pH=6.8 phosphate buffer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] The present invention is further illustrated by the following examples, which are intended to provide detailed explanations of the preparation and use of the crystalline forms of the present invention. It will be apparent to those skilled in the art that appropriate modifications of both materials and methods may be made without departing from the scope of the present invention.

[0039] The meanings of the abbreviations used in the present invention are as follows. XRPD: X-ray powder diffraction DSC: Differential scanning calorimetry TGA: Thermogravimetric analysis 1 HNMR: Liquid nuclear magnetic resonance spectroscopy DMSO: Dimethyl sulfoxide

[0040] The equipment and methods used to collect the data are as follows. The powder X-ray diffraction patterns in the present invention were collected using a Panalytical Empyrean powder X-ray diffractometer. The measurement conditions for powder X-ray diffraction in the present invention are as follows: X-ray source: Cu, Kα Kα1(Å):1.540598;Kα2(Å):1.544426 Kα2 / Kα1 intensity ratio: 0.50 Voltage: 45,000 volts (kV) Current: 40 milliamps (mA) Scanning range: 3.0 degrees to 40.0 degrees

[0041] The differential scanning calorimetry (DSC) pattern in the present invention was measured by a TA Q2000. The measurement conditions for the differential scanning calorimetry (DSC) in the present invention are as follows. Scanning speed: 10℃ / min unless otherwise specified Protective gas: N2

[0042] The thermogravimetric analysis (TGA) pattern in the present invention was measured using a TA Q500. The measurement conditions for the thermogravimetric analysis (TGA) in the present invention are as follows. Scanning speed: 10℃ / min Protective gas: N2

[0043] Hydrogen nuclear magnetic resonance spectrum data ( 1 HNMR) was measured using a Bruker Avance II DMX 400MHz nuclear magnetic resonance spectrometer. 1-5 mg of sample was weighed and dissolved in 0.5 mL of deuterated dimethyl sulfoxide (DMSO) to give a solution of 2-10 mg / mL.

[0044] The high performance liquid chromatography (HPLC) data for purity measurement in the present invention was measured using an Agilent 1260. The detector was a UV variable wavelength detector (VWD). The HPLC conditions used in the present invention are as follows. Column: Xbridge C8, 150 x 4.6 mm, 3.5 μm Mobile phase: A: 0.1% TFA in water B: 0.1% TFA in acetonitrile Gradient Slope

[0045] [Table 1] Flow rate: 1.0mL / min Injection volume: 3μL Column temperature: 40℃ Diluent: MeOH

[0046] The high performance liquid chromatography (HPLC) data for measuring the solubility was measured using an Agilent 1260. A UV variable wavelength detector (VWD) was used as the detector. The HPLC conditions in the present invention are as follows. Column: Xbridge C8, 150 x 4.6 mm, 5 μm Mobile phase: A: 0.1% TFA in water B: 0.1% TFA in acetonitrile Gradient Slope

[0047] [Table 2] Flow rate: 1.1mL / min Injection volume: 5μL Column temperature: 40℃ Diluent: MeOH EXAMPLES

[0048] Unless otherwise noted, the following examples are carried out at room temperature conditions.

[0049] In the following examples, the GSK1278863 raw material used was prepared based on conventional techniques, for example, by the method described in CN101505752B. In the following examples, the conventional solid means a solid of GSK1278863 obtained by reproducing the method described in CN101505752B by the present inventors.

[0050] [Examples 1 to 4] Preparation of crystalline form CS1 Example 1 6.4 mg of GSK1278863 raw material was weighed out and dissolved in 0.5 mL of tetrahydrofuran solvent, and then evaporated at room temperature for about 2 days to precipitate a solid. Analysis revealed that the obtained solid was crystalline form CS1, and its powder X-ray diffraction data are shown in Figure 1 and Table 1.

[0051] The hydrogen nuclear magnetic resonance spectrum pattern is shown in Figure 2. The nuclear magnetic data are 1HNMR(400MHz,d6-DMSO)δ 10.18(s,1H),4.62(s,2H),4.11(d,J=5.8Hz,2H),2.26(d,J=10.9Hz,4H),1.78(d ,J=12.6Hz,4H),1.60(t,J=11.8Hz,6H),1.27(d,J=12.9Hz,4H),1.13(s,2H).

[0052] The DSC curve of the crystal form CS1 obtained in this example is as shown in FIG. 3. When heated to about 242° C., one endothermic peak appears, which is the melting endothermic peak of the crystal form CS1.

[0053] The TGA curve of the crystalline form CS1 obtained in this example is shown in FIG. 4, and when heated to about 150° C., a mass loss of about 0.6% was observed.

[0054] [Table 3]

[0055] [Examples 2 to 3] The following mass of GSK1278863 raw material was weighed out and dissolved in the solvent shown in Table 2 below, and then evaporated at 50°C to obtain a solid. The solids obtained in Examples 2 and 3 are referred to as Sample 2 and Sample 3, respectively. Analysis revealed that both the solids of Sample 2 and Sample 3 were of the crystalline form CS1. Sample 2 was measured, and its powder X-ray diffraction data is shown in Figure 5 and Table 3.

[0056] [Table 4]

[0057] [Table 5]

[0058] Example 4 10.1 mg of GSK1278863 raw material was weighed out and dissolved in 0.5 mL of 1,4-dioxane solvent, 2.0 mL of poor solvent water was added dropwise, and the mixture was stirred at room temperature for 2 hours, centrifuged, and dried in vacuum to obtain a crystalline solid. Analysis showed that the obtained crystalline solid was crystalline form CS1.

[0059] [Examples 5-6] Preparation of crystalline form CS9 Example 5 4.6 mg of GSK1278863 raw material was weighed out and added to 0.7 mL of methyl tert-butyl ether solvent, and an equal mass of a polymer consisting of polycaprolactone, polyoxyethylene, polymethyl methacrylate, hydroxyethyl cellulose, and sodium alginate was added, and the mixture was evaporated at 50°C for about 1 day to precipitate a solid. Analysis revealed that the obtained solid was crystalline form CS9, and its powder X-ray diffraction data are shown in Figure 6 and Table 4.

[0060] The hydrogen nuclear magnetic resonance spectrum pattern is shown in Figure 7. The nuclear magnetic data are 1 HNMR(400MHz,d6-DMSO)δ 10.18(s,1H),4.62(s,2H),4.10(d,J=5.6Hz,2H),2.36-2.17(m,4H),1.78(d ,J=12.4Hz,4H),1.60(s,6H),1.34-1.21(m,4H),1.11(d,J=13.1Hz,2H).

[0061] [Table 6]

[0062] Example 6 Approximately 6.9 mg of GSK1278863 raw material was weighed out, dissolved in 0.7 mL of a 1:1 volumetric ratio mixture of ethyl acetate and ethanol, and evaporated at 50° C. for approximately 4 days to precipitate a solid. Analysis revealed that the resulting solid was crystalline form CS9.

[0063] The DSC curve of the crystalline form CS9 of the present invention is as shown in FIG. 8. When heated to about 145° C., one endothermic signal appeared, and when heated to about 237° C., one endothermic peak appeared. The TGA curve of the crystalline form CS9 of the present invention is shown in FIG. 9, and when heated to about 150° C., there was a mass loss of about 0.2%.

[0064] [Example 7] Comparison of hygroscopicity between crystalline forms CS1 and CS9 of the present invention and conventional solids The hygroscopicity of about 10 mg each of the crystalline forms CS1 and CS9 of the present invention and the conventional solid was measured by dynamic moisture sorption (DVS) at 25° C., and the experimental results are shown in Table 5. The DVS patterns of the crystalline forms CS1 and CS9 and the conventional solid are shown in Figures 10, 11 and 12, respectively.

[0065] [Table 7]

[0066] The results showed that under conditions of 25°C and 80% relative humidity, the crystalline forms CS1 and CS9 of the present invention hardly increased in weight due to moisture absorption, and were very stable and resistant to moisture absorption under high humidity conditions.In contrast, the conventional solids showed a large increase in weight due to moisture absorption under the same conditions, and were highly hygroscopic.

[0067] Since the low hygroscopic crystal form does not require special drying conditions during production, the drug production and post-treatment processes can be simplified, and it is suitable for industrial production. The crystal form CS1 and the crystal form CS9 of the present invention have lower hygroscopicity than conventional solids, and therefore the storage environment conditions can be relaxed, for example, there is no need to intentionally control the environmental humidity during storage, which leads to cost reduction and is also suitable from the viewpoint of long-term storage of drug substances and formulations.

[0068] [Example 8] Comparison of purity between crystalline forms CS1 and CS9 of the present invention and conventional solids The purity of the crystalline form CS1 of the present invention, the crystalline form CS9 and the conventional solid were measured by HPLC, and the results are shown in Table 6.

[0069] [Table 8]

[0070] Purity of a drug is important to ensure the efficacy and safety of the drug and to prevent the occurrence of adverse drug reactions. The impurity content of the conventional solid is very high at 18.94%, which results in a significantly lower drug content and reduced activity. The high impurity content also significantly increases toxic side effects. Therefore, the conventional solid drug substance cannot be directly used in the manufacture of formulations.

[0071] The high purity of the crystalline form of the present invention allows it to meet the stringent requirements for purity of drug substances in pharmaceutical preparations, making it suitable for subsequent formulation and pharmaceutical production.

[0072] [Example 9] Study on the stability of the crystalline form CS1 of the present invention The crystalline form CS1 of the present invention was stored in an open state at 25°C / 60% relative humidity, 40°C / 75% relative humidity, and 60°C / 75% relative humidity, and the XRPD comparison before and after storage was performed, respectively. The results are shown in Figures 13, 14, and 15, and the results are shown in Table 7.

[0073] [Table 9]

[0074] Furthermore, the inventors also studied the change in purity before and after storage of crystalline form CS1 in an open state for 3 months at 25° C. / 60% relative humidity, 40° C. / 75% relative humidity, and 60° C. / 75% relative humidity, and the results are shown in Table 8.

[0075] [Table 10]

[0076] Crystal form CS1 of the present invention was stored for at least 3 months at 25°C / 60% relative humidity, 40°C / 75% relative humidity, and 60°C / 75% relative humidity, and as a result, the crystal form did not change and the crystal form had good physical stability. In addition, the purity of the crystal form did not change much during storage, and the crystal form CS1 was found to be resistant to decomposition and to have good chemical stability.

[0077] As the most important active ingredient in medicine, it is extremely important that the crystalline form has good physical and chemical stability. Crystalline form CS1 has good physical stability, which ensures that the drug substance is not easily transformed into other crystalline forms during storage and formulation processes, and ensures the uniformity of sample quality.

[0078] In the storage of medicines, when the purity is low, the drug content is obviously low and the activity is reduced. In addition, when the purity is low, the toxic side effects may increase significantly, which may affect the efficacy and safety of the drug. The crystalline form CS1 has good chemical stability, so that the purity hardly changes during storage, which is important for ensuring the efficacy and safety of the drug and preventing the occurrence of adverse drug reactions. In addition, the stable crystalline form is easy to control in the crystallization process, and is less likely to produce impurities and mixed crystals, which is favorable from the viewpoint of industrial production.

[0079] The stability results for the drug substance crystalline form CS1 can also be used to predict its stability when made into a pharmaceutical formulation, making it possible to manufacture highly stable formulations.

[0080] [Example 10] Study on the stability of the crystalline form CS9 of the present invention The crystalline form CS9 of the present invention was stored in an open state at 25° C. / 60% relative humidity, 40° C. / 75% relative humidity, and 60° C. / 75% relative humidity, respectively, and the XRPD comparison before and after storage is shown in FIG. 16, FIG. 17, and FIG. 18, respectively, and the results are shown in Table 9.

[0081] [Table 11]

[0082] Furthermore, the inventors also investigated the change in purity before and after storage of crystalline form CS9 in an open state for one month at 25° C. / 60% relative humidity, 40° C. / 75% relative humidity and 60° C. / 75% relative humidity, and the results are shown in Table 10.

[0083] [Table 12]

[0084] The crystalline form CS9 of the present invention was stored at 25°C / 60% relative humidity, 40°C / 75% relative humidity, and 60°C / 75% relative humidity for at least 3 months, and the crystalline form did not change, and the purity hardly changed during storage for 1 month, indicating that the crystalline form CS9 has good stability, is unlikely to transition to other crystalline forms, and is unlikely to decompose. This makes it possible to manufacture highly stable formulations.

[0085] [Example 11] Dynamic solubility of crystalline forms CS1 and CS9 Based on the solubility measurement method described in the appendix of the Chinese Pharmacopoeia and the pH changes of each organ and part in the body, four solvent systems with pH values ​​ranging from 1.2 to 7.5 were prepared in the present invention, specifically, SGF (simulated gastric fluid) with pH 1.8, FeSSIF (simulated intestinal fluid in a fed state) with pH 5.0, FaSSIF (simulated intestinal fluid in a fasted state) with pH 6.5, and pure water.

[0086] The crystal forms CS1 and CS9 of the present invention were saturated with SGF, FeSSIF, FaSSIF, and pure water, respectively, and samples were taken at predetermined times to measure the dynamic solubility of the crystal forms CS1 and CS9 in the saturated solutions by high performance liquid chromatography (HPLC). The experimental results are shown in Tables 11 and 12.

[0087] [Table 13]

[0088] [Table 14]

[0089] Solubility is one of the important properties of drugs, which directly affects the absorption of drugs in the human body. Meanwhile, the solubility of drugs may vary greatly depending on the crystalline form, and the absorption behavior in the body may also change, leading to differences in bioavailability, which may ultimately affect the clinical safety and efficacy of drugs.

[0090] Compound (I) is a poorly soluble drug. For poorly soluble drugs, improving solubility becomes more important. Improving solubility contributes to improving the bioavailability of the drug and improving the usefulness of the drug. Furthermore, increasing solubility allows the dosage of the drug to be reduced while ensuring the efficacy of the drug, thereby reducing side effects of the drug and improving its safety.

[0091] The crystalline forms CS1 and CS9 of the present invention have good solubility in SGF, FeSSIF, FaSSIF and pure water, and are useful for ensuring good dissolution of the crystalline forms in the formulation, promoting effective absorption of the active ingredients of the formulation in the body, and achieving ideal bioavailability and efficacy of the medicine.

[0092] [Example 12] Study on the flowability of crystal forms CS1 and CS9 The flowability of the crystalline forms CS1 and CS9 of the present invention was evaluated by the compressibility index based on the United States Pharmacopeia (USP) 1174. After measuring the bulk density and tap density of the crystalline forms CS1 and CS9, the compressibility index was calculated, and the results are shown in Table 13.

[0093] 1. Test Method Samples: Crystalline form CS1 and Crystalline form CS9 Device: Tap Denser Container: 5ml graduated cylinder Vibration frequency: 500 times Bulk density = m / v0 (mass / volume before tapping) Tap density = m / v t (Mass / Volume after tapping) 2. Calculation formula: Compressibility index (%) = (tap density - bulk density) / tap density x 100% 3. Test Results

[0094] [Table 15]

[0095] The results show that the fluidity of crystalline form CS1 and crystalline form CS9 of the present invention can meet the requirements for formulation development, ensure the mixing uniformity and content uniformity of the formulation, reduce the weight variation of the dosage form, and ensure the quality of the product, and are therefore suitable for pharmaceutical use.

[0096] [Example 13] Study on crystal form CS1 and crystal form CS9 in the formulation 1. Preparation of GSK1278863 Tablets GSK1278863 crystalline form CS1 or crystalline form CS9, microcrystalline cellulose (crystalline cellulose), croscarmellose sodium and magnesium stearate were weighed out (content of each component is shown in Table 14) and mixed for 2 minutes. Tablets were pressed using a manual tablet press and a circular punch with a diameter of 7 mm was used to make tablets weighing 100 mg ± 1 mg at a pressure of 5 KN ± 1 KN. The tablets were placed in 35 cc HDPE bottles (one tablet per bottle), 1 g of desiccant was placed in each bottle, and the bottles were sealed with a sealing machine. Analysis showed that the crystalline form of the active ingredient did not change before and after preparation of the formulation.

[0097] [Table 16]

[0098] 2. In vitro dissolution test Regarding the in vitro dissolution state of the obtained tablets, the dissolution rate was measured under the following conditions based on "Method of measuring dissolution rate and release rate" of the Chinese Pharmacopoeia 2015 edition 0931. Dissolution medium: pH = 6.8 phosphate buffer + 1% sodium lauryl sulfate aqueous solution Dissolution method: Paddle method Volume of medium: 900mL Rotation speed: 75 rpm Medium temperature: 37℃

[0099] The dissolution profile of crystalline form CS1 is shown in Table 15 and Figure 19. The results show that the crystalline form of the present invention The tablets containing CS1 as the active ingredient had an average dissolution rate of 67.7% at 10 minutes and 95.2% at 60 minutes, which means that they have good dissolution rate and high dissolution rate.

[0100] Dissolution is a prerequisite for absorption. Good in vitro dissolution rate allows a drug to have a higher area under the curve (AUC) in vivo, which means that the drug is more absorbed and has better exposure characteristics in vivo, leading to higher bioavailability and drug efficacy. High in vitro dissolution rate allows a drug to have a shorter time to delivery (Tmax) and a higher peak concentration (Cmax) in vivo, which means that the drug can reach its maximum concentration quickly after administration, and the maximum concentration is high, ensuring that the drug is effective quickly.

[0101] [Table 17]

[0102] 3. Stability of crystalline forms CS1 and CS9 in formulations The tablets prepared above were stored for one month under the conditions of 40°C / 75% relative humidity. Analysis showed that there was no change in the crystal form in the tablets containing crystal form CS1 and crystal form CS9. The results are shown in Table 16. It was found that crystal form CS1 and crystal form CS9 have good stability in the formulation.

[0103] [Table 18]

[0104] The crystalline forms CS1 and CS9 of the present invention have good stability in formulations, and are unlikely to transform into other crystalline forms during the formulation process and storage of the formulation, thereby ensuring the uniformity of the quality of the pharmaceutical products.

[0105] The above examples are merely intended to illustrate the technical ideas and features of the present invention so that those skilled in the art can understand and practice the present invention, and are not intended to limit the present invention. Any equivalent modifications or improvements made within the scope of the present invention that do not depart from the spirit and scope of the present invention are included in the scope of the present invention.

Claims

1. Crystalline form CS1 of GSK1278863 is characterized by having characteristic peaks in a powder X-ray diffraction pattern at 2θ values ​​of 6.4°±0.2°, 7.5°±0.2°, and 7.9°±0.2°.

2. The crystalline form CS1 according to claim 1, characterized in that it has characteristic peaks in a powder X-ray diffraction pattern at one or more 2θ values ​​of 17.2°±0.2°, 21.0°±0.2°, 24.0°±0.2°, and 19.3°±0.2°.

3. (1) dissolving GSK1278863 in a cyclic ether solvent or a ketone solvent, and volatilizing and crystallizing the solvent at 10 to 50°C to obtain the target compound; or (2) GSK1278863 is dissolved in a cyclic ether solvent, a poor solvent is added to cause crystallization, and the crystals are then separated and dried to obtain the target compound. A method for producing crystalline form CS1 of GSK1278863, comprising:

4. In the above (1), the cyclic ether solvent is tetrahydrofuran, the ketone solvent is one of acetone and methyl isobutyl ketone or any combination thereof, and the volatilization temperature is room temperature or 50° C.; 4. The method according to claim 3, wherein in (2), the cyclic ether solvent is 1,4-dioxane, the poor solvent is water, and the crystallization time is 0.5 to 24 hours.

5. 5. The method according to claim 4, wherein in (1), the ketone solvent is acetone or methyl isobutyl ketone, and in (2), the crystallization time is 2 hours.

6. Crystalline form CS9 of GSK1278863 is characterized by having characteristic peaks in a powder X-ray diffraction pattern at 2θ values ​​of 4.6°±0.2°, 6.6°±0.2°, and 21.1°±0.2°.

7. 7. The crystalline form CS9 of claim 6, characterized in that it has characteristic peaks in a powder X-ray diffraction pattern at one or more 2θ values ​​of 9.4°±0.2°, 20.2°±0.2°, and 24.2°±0.2°.

8. (1) dissolving GSK1278863 in an ether-based solvent, adding a polymer, and volatilizing and crystallizing the polymer at 10 to 70°C to obtain the target compound; or (2) GSK1278863 is dissolved in a mixture of ester and alcohol solvents, and the mixture is evaporated and crystallized at 10 to 70°C to obtain the target compound. A method for producing crystalline form CS9 of GSK1278863, comprising:

9. In the above (1), the ether solvent is methyl tert-butyl ether, the polymer is a polymer consisting of equal masses of polycaprolactone, polyoxyethylene, polymethyl methacrylate, hydroxyethyl cellulose, and sodium alginate, and the volatilization temperature is 50° C.; The method according to claim 8, wherein in (2), the ester-based solvent is ethyl acetate, the alcohol-based solvent is ethanol, a volume ratio of the ester-based solvent to the alcohol-based solvent is 1:10 to 10:1, and the volatilization temperature is 50° C.

10. The method according to claim 9, wherein in (2), the volume ratio of the ester-based solvent to the alcohol-based solvent is 1:

1.

11. 13. A pharmaceutical composition comprising a therapeutically effective amount of crystalline form CS1 as defined in claim 1 or crystalline form CS9 as defined in claim 6 or any mixture thereof and a pharma- ceutically acceptable carrier, diluent or excipient.

12. 13. Use of crystalline form CS1 as defined in claim 1 or crystalline form CS9 as defined in claim 6 or any mixture thereof for the manufacture of a pharmaceutical formulation comprising a hypoxia inducible factor prolyl hydroxylase inhibitor.

13. 13. Use of crystalline form CS1 as defined in claim 1 or crystalline form CS9 as defined in claim 6 or any mixture thereof for the manufacture of a pharmaceutical preparation for the treatment and / or prevention of anemia.

Citation Information

Patent Citations

  • High-throughput formation, identification, and analysis of diverse solid-state forms

    JP2003519698A

  • Prolyl hydroxylase inhibitors

    JP2009541351A